Desempenho agronômico e qualidade tecnológica de cultivares de feijão-caupi em função da época de semeadura em Uberaba-MG - Almeida, Fernando da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Even in expanding to other regions of the country, most of cowpea cultivars were developed for the conditions of the northern and northeastern regions of Brazil. Thus, it is necessary to select cultivars which are more adapted to the environmental conditions of the cerrado, and also the best sowing dates in terms of productivity and technological quality of grain crops. The aim of this study was to evaluate the agronomic performance and technological quality of erect and semi-erect cowpea cultivars depending on sowing under rainfed conditions in Uberaba-MG. The experimental design was randomized blocks, in split plots with four replications. The plots were represented by three sowing dates (12/14/2012, 01/14/2013 and 02/14/2013). The subplots consisted on six cultivars (BRS Guariba Potengi BRS, BRS Cauamé, Novaera BRS, BRS Itaim Tumucumaque and BRS). The experimental subplot consisted on four five feet rows in length, spaced 0.40 meters, and the considered floor area was the two central rows. The agronomic performance and technologic quality of cowpea grain cultivars were influenced by environmental conditions of sowing dates. At sowing in December there was a significant vegetative growth of cowpea cultivars resulting in a lower yield. BRS Tumucumaque was the most productive in sowing done in January. In February, all cultivars had higher grain yields, especially for BRS and BRS Novaera Itaim, with productivity of 3,439 and 3,435 kg ha-1 respectively

Mesmo estando em franca expansão para outras regiões do país, a maioria das cultivares de feijão-caupi foram desenvolvidas para as condições das regiões norte e nordeste do Brasil. Assim, existe a necessidade da seleção de cultivares mais adaptadas às condições edafoclimáticas do cerrado, mas também as melhores épocas de semeadura em termos de produtividade e qualidade tecnológica dos grãos da espécie. O objetivo do trabalho foi avaliar o desempenho agronômico e a qualidade tecnológica de cultivares de feijão-caupi de porte ereto e semiereto em função da época de semeadura em condições de sequeiro em Uberaba-MG. O delineamento experimental foi de blocos casualizados, com parcelas subdivididas e quatro repetições. As parcelas foram representadas por três épocas de semeadura (14/12/2012, 14/01/2013 e 14/02/2013). As subparcelas foram constituídas por seis cultivares (BRS Guariba, BRS Potengi, BRS Cauamé, BRS Novaera, BRS Itaim e BRS Tumucumaque). A subparcela experimental foi formada por quatro fileiras de cinco metros de comprimento espaçadas em 0,40 metros, sendo considerada como área útil as duas fileiras centrais. O desempenho agronômico e a qualidade tecnológica dos grãos das cultivares de feijão-caupi foram influenciados pelas condições edafoclimáticas das épocas de semeadura. Na semeadura em dezembro ocorreu um desenvolvimento vegetativo expressivo das cultivares de feijão-caupi acarretando uma menor produtividade de grãos. A cultivar BRS Tumucumaque foi a mais produtiva na semeadura realizada em janeiro. Na semeadura realizada em fevereiro, todas as cultivares obtiveram maiores produtividades de grãos, com destaque para a BRS Itaim e BRS Novaera, com produtividade de 3.439 e 3.435 kg ha-1 respectivamente
Keywords: Feijão-de-corda; Feijão - Cultivo; Feijão - Semeadura; Produtividade agrícola; Desempenho; Beans